Plantinventering och plantkontroll med digitala bilder från helikopter - Orgum, Jonas (2008)
This study was carried out as a commission from Holmen Skog, district "Egen skog" in Norrköping. During October 2006 several stands were inventoried by aerial photos from helicopter. The stands were those for which the next action proposed was plant inventory or plant check. The photos were interpreted and the number of stems was calculated. Of the stands in the inventory, 16 were chosen for plant inventory and 18 for plant check. A field survey was performed for these stands in late November and December in 2006 to study the performance of the helicopter inventory. The helicopter used in the inventory was model EC 120 which was equipped with an advanced gyro-stabilized camera. The photography started when the GPS registered that the position of the helicopter was inside the border of the object. For the plant inventory the locations of 84 pictures were identified and visited in field. At the location of the photography a circular sample plot with a radius of 5 meters was placed and within the area of the sample plot the number of plants as well as the main crop plants was counted. Within the plant inventory a conventional survey was also performed (20 sample plots with a radius of 1.785 meters) for a comparison with the results from the helicopter inventory, especially for precision statements. The study of the plant check was performed on a stand level due to the difficulties of finding the location of the photography. The field survey within the plant control was done by an objective inventory with circular sample plots with a radius of 3 meters. In the study, functions for prediction of the number of main crop plants from the total amount of stems interpreted in the picture were produced. It was found that these functions could predict the number of main crop plants with reasonable precision. This is necessary for approve a regeneration or not, as it is the number of main crop plants that is used for decision. For the plant inventory the function for estimating the number of main crop plants from the total number of plants in the photography is, for a given photography, Main crop plant = 3381 – 60,5* 1000/yphotographtheinplants )489(=S and for the plant control on a stand level the function is, Main crop plant = 3218 – 2485* 1000/plants in the photography )287(=S For a reasonable coverage of stands and sufficient accuracy for management decisions, approximately 10 photos (each with an area of about 350 m2 ) seemed to correspond with the conventional survey. The cost for the conventional survey is estimated to 100 Sw. crowns per hectare while the cost for the helicopter inventory is approximately 175 Sw. crowns per hectare. This means that the conventional survey method is more cost efficient than the helicopter method.